Feasibility of rehabilitating timber bridges with mechanically fastened FRP strips - Oliva, Michael; Schorer, Alyssa E.; Bank, Lawrence C.; Rammer, Douglas R.; Wacker, James P. (Midwest Regional University Transportation Center, 2008)
Many timber trestle railroad bridges in Wisconsin have experienced deterioration and are in need of rehabilitation. In addition, the railroad industry is increasing the weights of cars. The combined effect of heavier loads and deterioration threatens to cut short the service life of timber bridges. One of the most critical problems that has been identified was the overloading of timber piles in bridges, which can be remedied by creating a stiffer pile cap. The goal of this investigation was to show that mechanically fastened fiber reinforced polymer (MF-FRP) strips fastened to timber with screws can be used to create composite action between two beams in flexure or truss action between two deep beams. Ultimately this may help redistribute the loads to piles when FRP strips are used as struts on cap beams over short spans. Several test series were conducted with beams in flexure, deep beams over short spans, and full scale specimens to determine the manner in which FRP strips improved the members' performance. Tests were conducted over various widths of beams and lengths of spans to investigate how the geometry affected the strengthening's ability to create composite action. Next, the MF-FRP was tested on deep beams to determine if composite action was maintained. Lastly, full scale tests simulating a pile cap over 5 piles were run to see if composite action improved load distribution to piles. Mechanically fastened FRP strips were found to be effective in developing composite action in slender beams in flexure, meaning the stiffness of the system was increased by using MF-FRP strips. This MF-FRP method showed great potential for creating composite, stiffer double pile caps.
192 p.
Keywords: Fiber reinforced polymers; Mechanically harnessed joints; Railroad bridges; Strengthening (Maintenance); Wisconsin; Wooden bridges; Pile caps; Rehabilitation (Maintenance); Composite construction